2020
DOI: 10.1177/1741143220935455
|View full text |Cite
|
Sign up to set email alerts
|

Identity politics: Why African American women are missing in administrative leadership in public higher education

Abstract: There is an exiguous representation of African American women in leadership positions at institutions of higher education. This study examines the experiences related to the retention of Black women administrators at Predominantly White Institutions through a qualitative phenomenological lens. This study explored the experiences of five African American women administrators at public institutions across the USA. The participants highlighted the impact of Black Tax, the presentation of their authentic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…For example, African American chief administrators make up 8% of all roles whereas White chief administrators make up 83% (Espinosa et al, 2017). African American women report experiencing specific barriers to advancement that are uniquely different than those experienced by African Americans or women, separately (Townsend, 2021). Quantitative data backs this up; Hebner et al (2018) found that nonwhite female chief executives earn the least out of the following groups: nonwhite male executives, white female executives, and white male executives.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, African American chief administrators make up 8% of all roles whereas White chief administrators make up 83% (Espinosa et al, 2017). African American women report experiencing specific barriers to advancement that are uniquely different than those experienced by African Americans or women, separately (Townsend, 2021). Quantitative data backs this up; Hebner et al (2018) found that nonwhite female chief executives earn the least out of the following groups: nonwhite male executives, white female executives, and white male executives.…”
Section: Limitationsmentioning
confidence: 99%
“…Few research studies have focused on Black Women administrators and the ways in which they lead. Rather, studies have focused on the underrepresentation (Flowers, 2003;Harper, 2005;and Townsend, 2021), isolation (Patitu, 2003;Gregory, 2001;and Willis, et al, 2019), and marginalization (Bazner, 2021;Lloyd-Jones, 2014;and Mitchell, et al, 2014) of Black Women in higher education. Limited research also discusses the experiences of Black Women administrators at Historically Black Colleges and Universities (HBCUs), while rarely highlighting their experiences in a positive light at predominantly White institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars applied CRT to educational environments “… to foreground race and racism in the research as well as challenge the traditional paradigms, methods, texts, and separate discourse on race, gender, and class by showing how these social constructs intersect to impact communities of color” (Solorzano et al., 2000, p. 63; see also Ladson‐Billings, 1998). Like Black feminist thought, CRT is a mechanism through which Black women can uniquely (re)define and counter‐narrate their stories, disrupt dominant narratives, and confront gendered racism (Essed, 1991) in higher education scholarship and practice (Boss et al., 2021; Townsend, 2021).…”
Section: Introductionmentioning
confidence: 99%